2023
DOI: 10.1002/adma.202305472
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy for Developing Ultrasensitive “Transistor‐Like” Thermochromic Fluorescent Materials for Multilevel Information Encryption

Abstract: Thermochromic fluorescent materials (TFMs) exhibit great potential in information encryption applications, but are limited by low thermosensitivity, poor color tunability, and a wide temperature‐responsive range. Herein, a novel strategy for constructing highly sensitive TFMs with tunable emission (450‐650 nm) toward multilevel information encryption was proposed, which employed polarity‐sensitive fluorophores with D‐A‐D type structures as emitters and long‐chain alkanes as thermosensitive loading matrixes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It has been reported that stimuli such as solvents, heat, force or light could change the emission colors of specific emitters. 26–30 However, these external stimuli work well only when the emitters are in solution or solid state (powder or doped film). Because of the sandwich-like characteristics of the solid-state structure of OLEDs, neither solvents nor external forces are present, and the devices are also unable to withstand external heating.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that stimuli such as solvents, heat, force or light could change the emission colors of specific emitters. 26–30 However, these external stimuli work well only when the emitters are in solution or solid state (powder or doped film). Because of the sandwich-like characteristics of the solid-state structure of OLEDs, neither solvents nor external forces are present, and the devices are also unable to withstand external heating.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the RBPU elastomers were characterized by 1 H NMR and FT-IR spectra. Taking RBPU-8 as an example, the 1 H NMR spectra clearly showed typical characteristic peaks of IPDI, PTMEG, PDM, and RBNH 2 in the polymeric backbones, indicating its successful synthesis (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, efforts to address the issue of singular ultraviolet decoding of fluorescent anti-counterfeiting labels mainly focus on the construction of dual encryption systems, which can be achieved by controlling the fluorescence color for dynamic anti-counterfeiting and utilizing deformable substrate materials to conceal the loaded information. As the former is relatively difficult, 19–21 modulation of substrate materials with fluorescent patterns to realize dual encryption by adding the spatial dimension becomes an effective strategy. Intelligent gel materials exhibit outstanding stimulus-responsiveness, stability, and modifiability, and are easy to integrate with fluorescence emitters.…”
Section: Introductionmentioning
confidence: 99%